Effect of incarcerated HF on the exohedral chemical reactivity of HF@C60. Issue 80 (24th August 2017) - Vidal, Sara; Izquierdo, Marta; Alom, Shamim; Garcia-Borràs, Marc; Filippone, Salvatore; Osuna, Sílvia; Solà, Miquel; Whitby, Richard J.; Martín, Nazario
Abstract : The first chemical modification on the brand new endohedral HF@C60 is reported. Abstract : The first chemical modification on the brand new endohedral HF@C60 is reported. In particular, the isomerization from optically pure (2 S, 5 S )- cis -pyrrolidino[3, 4:1, 2][60]fullerene2b to (2 S, 5 R )- trans -pyrrolidino[3, 4:1, 2][60]fullerene2b has been studied and compared with empty C60 (2a ) and endohedral H2 O@C60 (3 ). The comparative study shows a kinetic order for the isomerization process of H2 O@C60 > HF@C60 > C60, thus confirming the effect of the incarcerated species on the zwitterionic intermediate stability.